2016
DOI: 10.1371/journal.pone.0146411
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Preferable Alternative Route to Right Internal Jugular Vein for Placing Tunneled Dialysis Catheters: Right External Jugular Vein versus Left Internal Jugular Vein

Abstract: BackgroundRight internal jugular vein (IJV) is a preferred access route for tunneled (cuffed) dialysis catheters (TDCs), and both right external jugular vein (EJV) and left IJV are alternative routes for patients in case the right IJV isn’t available for TDC placement. This retrospective study aimed to determine if a disparity exists between the two alternative routes in hemodialysis patients in terms of outcomes of TDCs.Methods49 hemodialysis patients who required TDCs through right EJV (n = 21) or left IJV (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Although A-V fistula and A-V graft are preferential types of vascular access, tunneled CVC provides an important alternative for hemodialysis patients who have a poor vascular condition or who are waiting for an alternative access to mature 1 , 2 . Over the past 10 years, CVCs have played an increasing role in hemodialysis because they have advantages over arteriovenous access including the relative ease of placement, removal, replacement and the possibility for immediate use 1 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Although A-V fistula and A-V graft are preferential types of vascular access, tunneled CVC provides an important alternative for hemodialysis patients who have a poor vascular condition or who are waiting for an alternative access to mature 1 , 2 . Over the past 10 years, CVCs have played an increasing role in hemodialysis because they have advantages over arteriovenous access including the relative ease of placement, removal, replacement and the possibility for immediate use 1 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the catheter-related bloodstream infection is several times more common than AVF and AVG, and 12-month rate of catheter-related bloodstream infection is approximately 50% among patients who receive HD 26 , 27 , and infection is the second most common cause of hospitalization and death among HD patients 28 , 29 . Furthermore, the incidence of catheter-related infection can reach 0.28–1.7 episodes per 1000 CVC days 30 32 . Thus, strategies are needed to reduce the rate of VA-induced infection.…”
Section: Discussionmentioning
confidence: 99%
“…All patients had a history of prior TCCs insertion, and the reasons for the in-hospital TCC replacement were as follows: catheter dysfunction ( n = 15), long-term duration and regular catheter exchange ( n = 6), symptomatic extremity and/or facial edema ( n = 5), catheter extrusion ( n = 1). TCC dysfunction was defined as an inability to maintain adequate extracorporeal blood flow without prolonging the prescribed HD treatment, inability to flush the locking solution from TCC lines, blood flow rate <300 ml/min, arterial pressure <250 mmHg, high venous pressure >250 mmHg, or the need for TCC lines reversal ( 2 , 16 , 17 ). All the lesions were confirmed through MSCTV.…”
Section: Methodsmentioning
confidence: 99%